Gut microbiome in Schizophrenia: Altered functional pathways related to immune modulation and atherosclerotic risk - Nguyen, Tanya T.; Kosciolek, Tomasz; Daly, Rebecca E.; Vázquez-Baeza, Yoshiki; Swafford, Austin; Knight, Rob; Jeste, Dilip V. (Brain, behavior, and immunity, 2021)
•SZ is associated with altered gut microbial composition and functional potential.•Models based on the gut microbiome differentiated SZ from NCs with high accuracy.•Lachnospiraceae was associated with SZ.•TMAO reductase and Kdo2-lipid A biosynthesis functional pathways were altered in SZ.•Pathways were associated with inflammatory cytokines and risk for coronary heart disease in SZ. Emerging evidence has linked the gut microbiome changes to schizophrenia. However, there has been limited research into the functional pathways by which the gut microbiota contributes to the phenotype of persons with chronic schizophrenia. We characterized the composition and functional potential of the gut microbiota in 48 individuals with chronic schizophrenia and 48 matched (sequencing plate, age, sex, BMI, and antibiotic use) non-psychiatric comparison subjects (NCs) using 16S rRNA sequencing. Patients with schizophrenia demonstrated significant beta-diversity differences in microbial composition and predicted genetic functional potential compared to NCs. Alpha-diversity of taxa and functional pathways were not different between groups. Random forests analyses revealed that the microbiome predicts differentiation of patients with schizophrenia from NCs using taxa (75% accuracy) and functional profiles (67% accuracy for KEGG orthologs, 70% for MetaCyc pathways). We utilized a new compositionally-aware method incorporating reference frames to identify differentially abundant microbes and pathways, which revealed that Lachnospiraceae is associated with schizophrenia. Functional pathways related to trimethylamine-N-oxide reductase and Kdo2-lipid A biosynthesis were altered in schizophrenia. These metabolic pathways were associated with inflammatory cytokines and risk for coronary heart disease in schizophrenia. Findings suggest potential mechanisms by which the microbiota may impact the pathophysiology of the disease through modulation of functional pathways related to immune signaling/response and lipid and glucose regulation to be further investigated in future studies.